The Routledge companion to terrorism studies: new perspectives and topics - Abrahms, Max (Routledge, Taylor & Francis Group, 2025)
"Although the literature on terrorism is vast, there are many holes in it. This book helps to fill these lacunae with entries from top terrorism scholars and counterterrorism practitioners in the world. Grouped thematically by terrorist actors, conflict zones, major attacks, terrorist behaviours, militant group dynamics, terrorist consequences, and counterterrorism approaches, the entries cover a range of topics fundamental to understanding the contemporary terrorism threat and approaches to combating it. Truly global in scope, the book is an ideal reference for anyone interested in these topics from a variety of disciplinary perspectives. Providing incisive analysis on timely topics related to terrorism and counterterrorism, this volume will be essential reading for students, scholars, and practitioners in security studies"--